CM Servisystem Enterprise / Rehasmely Yuhana Razali... [et al.] - Razali, Rehasmely Yuhana; Shuib, Nuradilah; Ahmad, Nikmah Nidayu; Abd. Majid, Wan Musrhida; Che Omar, Asmarina (2001)
Nowadays, Malaysian has penetrated to the new era of technology. The development of technology and entrepreneurship industry at Malaysian has produced a lot of new entrepreneurs. Because of that we take this initiative not to be left behind and to be competitive in the market. It is one of the ways we can support Malaysia to achieve 2020 vision. Our company or business will be establish on the 1st January 2004 and we have decided to name our company as ' CM Servisystem Ent. '. It is the partnership company that has fully owned by bumiputera. Our business is divided into two sections, there is cleaning and maintenance whereby the location that we had chosen is at No. 13, Ground Floor, Lengkok Cempaka 1, Persiaran Cempaka, 08000 Bandar Amanjaya., Sungai Petani, Kedah Darul Aman. There are many factors that influence us to select this form of business. One of them is because it is easy to get financial and support other capital sources that can be obtained from partners. Beside, we can see a lot of ideas, capability and the skill then can be integrated for the development our business. The other objective that encourages us we to doing this business are because of its high potential in the future. we can see that there is a few among bumiputera operate this type of business.